EFEKTIVITAS PENILAIAN PEMBELAJARAN MATEMATIKA SELAMA MASA PANDEMI COVID-19 SDK NDONA 2 KECAMATAN NDONA KABUPATEN ENDE - Maria Ana; Theodosia Ndole (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2021)
This study aims to determine the effectiveness of the assessment of mathematics learning during the COVID-19 pandemic at SDK Ndona 2, Ndona District, Ende Regency. This type of research is qualitative research with data collection techniques in this study carried out by means of observation, interviews, and documentation. After the data was collected, the data were analyzed qualitatively. The results of this study indicate that the effectiveness of assessing mathematics learning during the COVID-19 pandemic only focuses on the cognitive assessment of students, therefore teachers have other techniques in carrying out mathematics learning assessments so that they can provide a real picture of students' abilities. The conclusion from the results of this study is that during this pandemic the assessment of mathematics learning has been effective. This is because the assignment given by the teacher is not done by students but is served by someone else (parents, siblings)